PEMBUATAN IKLAN ANIMASI UNTUK DOMPET SOSIAL MADANI - Rifqi Muhammad Nabil; Sri Supriyatini; Desak Putu Yogi Antari Tirta Yasa (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
So many become unemployed due to not meeting the criteria desired by the company. Educational degree, amount of experience, and high ability, as well as the number of skills are the basic considerations for a company to accept prospective workers. Therefore, the government has formed a policy that can equip students before facing the realities of the world of work, namely the Independent Campus Program. This program is designed and created to provide students with the opportunity to experience the world of work first-hand in order to hone their soft skills and hard skills according to their respective interests and expertise. On this occasion, the author again partnered with Dompet Sosial Madani (DSM) to solve the cases encountered. Making animated advertisements is the method that the author chooses to solve the cases encountered. This thesis will thoroughly discuss the author's process in creating and designing animated advertisements from scratch. Making this animated commercial is the author's debut in making animation. The author's reason for choosing animated advertisements is to attract attention and build connections in the minds of the audience regarding the DSM program and who DSM is. The purpose of making this animated advertisement is to assist DSM in promoting its programs with more interesting content than most other social institutions and to hone the abilities and creativity of writers. By making this animated advertisement, the author hopes to increase the existence of DSM in society so that it can help more people in need with DSM programs in the future. The author can say that there are many opportunities to promote goods or services, but not everyone has the knowledge and skills to design or develop visual media, especially animation. The creation of DSM animated commercials is the author's good intention to assist DSM in carrying out its humanitarian programs. As the saying goes, good knowledge is knowledge that benefits many people. Through the MBKM Independent Study/Project Program, the author hopes to gain knowledge that will be useful for many people and later in society.